Structural insights into the distinctive RNA recognition and therapeutic potentials of RIG‐I‐like receptors. Issue 1 (21st July 2021) - Batool, Maria; Kim, Moon Suk; Choi, Sangdun
Abstract: RNA viruses, including the coronavirus, develop a unique strategy to evade the host immune response by interrupting the normal function of cytosolic retinoic acid‐inducible gene‐I (RIG‐I)‐like receptors (RLRs). RLRs rapidly detect atypical nucleic acids, thereby triggering the antiviral innate immune signaling cascade and subsequently activates the interferons transcription and induction of other proinflammatory cytokines and chemokines. Nonetheless, these receptors are manipulated by viral proteins to subvert the host immune system and sustain the infectivity and replication potential of the virus. RIG‐I senses the single‐stranded, double‐stranded, and short double‐stranded RNAs and recognizes the key signature, a 5′‐triphosphate moiety, at the blunt end of the viral RNA. Meanwhile, the melanoma differentiation‐associated gene 5 (MDA5) is triggered by longer double stranded RNAs, messenger RNAs lacking 2′‐ O ‐methylation in their 5′‐cap, and RNA aggregates. Therefore, structural insights into the nucleic‐acid‐sensing and downstream signaling mechanisms of these receptors hold great promise for developing effective antiviral therapeutic interventions. This review highlights the critical roles played by RLRs in viral infections as well as their ligand recognition mechanisms. In addition, we highlight the crosstalk between the toll‐like receptors and RLRs and provide a comprehensive overview of RLR‐associated diseases as well as the therapeutic potential of RLRs for the development of antiviral‐drugs. Moreover, we believe that these RLR‐based antivirals will serve as a step toward countering the recent coronavirus disease 2019 pandemic.